PREVALENCE OF OVERACTIVE BLADDER IN FEMALES OF WORKING CLASS - Khawar Ali; Athar Mahmood; Javaria Farooq (Journal of University Medical & Dental College, 2017)
INTRODUCTION: Overactive bladder (OAB) has been deﬁned by the International Continence Society(ICS) as a complex of symptoms characterized by urgency, with or without urge incontinence, usually with frequency and nocturia, in the absence of proven infection or other obvious pathology[1].Urodynamically OAB is characterized by involuntary detrusor contraction.OAB has a profound effect on quality of life(QoL).[,2, 3, 4, 5]. OAB has a negative impact on economy of a person [4,5,6]. OAB is prevalent in both sexes and is affected by age , obesity , smoking , eating and drinking habits[4,5,6,7,8,9,10]. OAB has been studied much in the recent years. Much emphasis has been laid on the pathophysiology and management of the disease. Despite all that,OAB is usually underdiagnosed and undermanaged[7-12].According to a population-based study by Milsom et al [12] in 6 countries. the prevalence of OAB in Europe has been estimated to be 17.4% and 15.6% for women and men respectively, with an overall prevalence of 16.6%. According to the NOBLE study prevalence of OAB was 16.0% in men and 16.9% in women [3].In a recent study conducted in Japan overall OAB prevalence was 9.3% .The prevalence of OAB in men and women was 9.7% and 8.9%, respectively. According to some studies OAB has a prevalence as high as 30% to 53% [10,14], while one study showed 8% [15], and one study showed 2% [16]. All these studies had differences and limitations in their methodology. Despite of so much research work on OAB, it has rarely been studied in working class females who are adversely affected by OAB.Our study purpose is to look for the prevalence of OAB in this class.